Outcomes following temporalis tendon transfer in irradiated patients - Griffin, Garrett R. (Arch Facial Plast Surg, 2012)
OBJECTIVE: To compare objective outcomes and complications following temporalis tendon transfer in patients with and without a history of radiation to the parotid bed. METHODS: Retrospective chart review comparing dynamic movement of the oral commissure and resting symmetry achieved in 7 irradiated (group R) and 7 non-irradiated (group N) patients after temporalis tendon transfer for unilateral facial paralysis. RESULTS: There were no significant differences between the two groups of patients in terms of age, additional facial reanimative procedures, or baseline lip position. Post-operatively, good resting symmetry was achieved in both groups. Mean commissure excursion was significantly inferior in the irradiated group of patients (−1.5 mm in group R vs. 2.1 mm in group N; p<0.05). Two patients in the irradiated group experienced surgical site infections requiring hospital admission and eventual debridement of their tendon transfers. CONCLUSION: Temporalis tendon transfer appears to produce less dynamic movement in patients that have received radiation to the parotid bed, and these patients may also be at higher risk of postoperative infection. Temporalis tendon transfer can achieve good resting symmetry in both irradiated and non-irradiated patients.